Effect of relining, water storage and cyclic loading on the flexural strength of a denture base acrylic resin - dos Santos Nunes Reis, Jose Mauricio; Eduardo Vergani, Carlos; Claudia Pavarina, Ana; Teresinha Giampaolo, Eunice; Lucia Machado, Ana (Elsevier B.V., 2006)
Objectives: This study investigated the effect of relining, water storage and cyclic loading on the ultimate flexural strength (FSU) and on the flexural strength at the proportional limit (FSPl) of a denture base acrylic resin (Lucitone 550-L).Methods: Rectangular bars of L were made (64 mm x 10 mm x 2 mm) and relined (1.3 mm) with four relining resins (Kooliner-K, Ufi Gel Hard-UGH, Tokuso Rebase Fast-TR and New Truliner-NT). In addition, specimens relined with L and intact L specimens were made (64 mm x 10 mm x 3.3 mm). A three-point flexural test was applied on the specimens (n = 10) after (1) polymerization; (2) water storage (30 days); (3) cyclic loading (10,000 cycles at 5 Hz) and (4) water storage (30 days) + cyclic loading. Data (MPa) were analyzed with three-way ANOVA and Tukey's HSD tests (alpha = 0.05). To test for a possible correlation between FSU and FSPl, a linear regression coefficient 'r' was calculated.Results: After water storage, L-UGH and L-TR demonstrated an increased FSU (41.4950.64 MPa and 49.95-57.36 MPa, respectively) (P < 0.05). Only L-TR demonstrated an increased FSPl (20.58-24.21 MPa) after water storage (P < 0.05). L-L had the highest FSU (between 78.57 and 85.09 MPa) and FSPl (between 31.30 and 34.17 MPa) (P < 0.05). The cyclic loading decreased the FSU and FSPl of all materials (P < 0.05). Regression analysis showed a strong linear correlation between the two variables (r = 0.941).Conclusions: Water storage improved the FSU of L-UGH and L-TR and the FSPl of L-TR. L-L produced the highest FSU and FSPl. The FSU and FSPl of all materials were detrimentally influenced by cyclic loading.
Keywords: flexural strength; acrylic resins; relining; water storage; cyclic loading